2020
DOI: 10.1088/1361-6641/ab94d9
|View full text |Cite
|
Sign up to set email alerts
|

Power loss mechanisms in n-type modulation-doped AlGaAs/GaAsBi quantum well heterostructures

Abstract: We report on the power loss mechanisms of hot electrons in as-grown and annealed n-type modulation-doped Al 0.15 Ga 0.85 As/GaAs 1-x Bi x (x = 0 and 0.04) quantum well structures considering acoustic phonon interactions via the deformation potential (non-polar) and piezoelectric (polar) scatterings. The two-dimensional (2D) electron gas is heated by applying various electric fields under a steady-state magnetic field, and the effect of the applied electric field on the Shubnikov de Haas (SdH) oscillations is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The QW GaAsBi layer contained %4% Bi. [5,[15][16][17] The sample was fabricated in Hall bar geometry using conventional photolithographic methods for high-electric field measurements. In the measurement, Hall arm with of 750 μm (length) Â 100 μm (width) was used.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The QW GaAsBi layer contained %4% Bi. [5,[15][16][17] The sample was fabricated in Hall bar geometry using conventional photolithographic methods for high-electric field measurements. In the measurement, Hall arm with of 750 μm (length) Â 100 μm (width) was used.…”
Section: Methodsmentioning
confidence: 99%
“…The energy separation between the first quantized energy level in QW and barrier layer's conduction band edge as ≈0.159 eV is much lower than the difference between the first quantized energy level at the Γ valley and conduction band edge of the L satellite valley of GaAsBi QW layer as being ≈0.263 eV. [ 5,15–17 ] Thus, hot electrons in the central valley of the QW start transferring to the central valley of the barrier layer as a result of RST then as increasing electron temperature, and both RST and IVT contribute to the electronic transport of hot electrons. In order to clarify the amount of the transferred electrons, the transition rate between the layers should be calculated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ludewig et al showed that this AlGaAs layer for the barrier is good at carrier confinement within quantum well (QW) layers [12]. Contrary to bulk and epilayer GaAsBi materials, there are limited studies on the investigation of the electrical transport mechanism of the low dimensional GaAsBi structures apart from our previously published papers [13,14]. In our previous studies on n-type modulation doped GaAsBi/ AlGaAs QW structures, we determined fundamental electrical transport parameters such as electron effective mass, quantum mobility, the carrier density in QW, Fermi level position, and deformation potential energy at low temperatures.…”
Section: Introductionmentioning
confidence: 99%